Acceptance of Online Education in Portugal and in the World: Before and During Covid-19 - Pascoal, R. (Kriativ.Tech, 2020)
The model of education in Portugal and around the world is changing. Online education is not accepted by all, and it loses quality whether or not it is in a pandemic scenario. Therefore, this work of analysis and discussion aims to find out which the measures are most appropriate to be adopted to protect public health and at the same time maintain the quality of teaching and acceptance by all. The solution is based on a mixed teaching model, that is, some face-to-face classes and other in distance and e-learning classes, because online education has worse learning results than faceto-face education, according to experts in the field.